2011
DOI: 10.1007/s00360-011-0596-9
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic effects of prolonged starvation and refeeding in sturgeon and rainbow trout

Abstract: The present study examines the particular metabolic strategies of the sturgeon Acipenser naccarii in facing a period of prolonged starvation (72 days) and subsequent refeeding (60 days) compared to the trout Oncorhynchus mykiss response under similar conditions. Plasma metabolites, endogenous reserves, and the activity of intermediate enzymes in liver and white muscle were evaluated. This study shows the mobilization of tissue reserves during a starvation period in both species with an associated enzymatic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
109
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 64 publications
22
109
2
Order By: Relevance
“…Based on the present results, starvation periods had effects on plasma total protein, albumin and globulin; in fact these parameters in the deprived groups were significantly higher than the control group. Similar to the results of present study, Hung et al (1997), Power et al (2000), Furné et al (2012) and Ashouri et al (2013) have reported an increase in plasma protein of several fish species as a result of starvation. In contrast, some studies on teleosts fish have reported the increased levels of plasma protein in response to food deprivation (Heming & Paleczny 1987;Friedrich & Stepanowska 2001;Polakof et al 2006;Costas et al 2011;Perez-Jimenez et al 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on the present results, starvation periods had effects on plasma total protein, albumin and globulin; in fact these parameters in the deprived groups were significantly higher than the control group. Similar to the results of present study, Hung et al (1997), Power et al (2000), Furné et al (2012) and Ashouri et al (2013) have reported an increase in plasma protein of several fish species as a result of starvation. In contrast, some studies on teleosts fish have reported the increased levels of plasma protein in response to food deprivation (Heming & Paleczny 1987;Friedrich & Stepanowska 2001;Polakof et al 2006;Costas et al 2011;Perez-Jimenez et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Pérez-Jimenez et al (2007) have demonstrated that starvation can decrease in plasma total triglyceride and cholesterol levels during food deprivation periods. Numerous studies have reported a reduction in plasma triglyceride and cholesterol levels during starvation (Hung et al 1997;Polakof et al 2006;Pérez-Jiménez et al 2007;Costas et al 2011;Furné et al 2012;Perez-Jimenez et al 2012). The outcome of the present results and other studies revealed that there will be a decline in glycogen reserves, during the food deprivation period followed by decreased plasma glucose level.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, in comparison to 2S and 4S groups, 8S group showed higher plasma total protein levels than those of the two other groups. Furné et al (2012) observed different effects on plasma total protein levels during starvation period for 72 days in both Adriatic sturgeon, Acipenser naccarii Bonaparte, 1836, and rainbow trout. During starvation, sturgeons are believed to use protein reserves as the third priority after glycogen and fat for obtaining the required energy for metabolism (Hung et al 1997), which is in agreement with the results acquired in this study.…”
Section: Discussionmentioning
confidence: 85%
“…However, following a longer period of fasting (14 days), the muscular reserves of lipids are mobilized, thus increasing levels of plasmatic triglycerides. According to Furné et al (2012), the mobilization of hepatic reserves of lipids is related to species, the tissue of the reserves, and the strategies via which a particular species can mobilize other energy sources.…”
Section: ;mentioning
confidence: 99%